Transient osteoporosis of the knee. - Nikolaou, Vassilios S; Pilichou, Anastasia; Korres, Demitrios; Efstathopoulos, Nicolas (Orthopedics, 2008)
A 52-year-old man presented with a 3-week history of right knee pain, significant enough to prevent weight bearing. There was no history of knee injury or disease. On knee examination, an effusion and medial joint line tenderness was noted. Knee range of motion was full, but painful. Radiographs revealed minor osteoarthritic changes. Laboratory values were within normal limits, including those associated with infection. Magnetic resonance imaging showed decreased signal intensity on T1-weighted images within the medial femoral condyle and corresponding increased signal intensity on T2-weighted consistent with bone marrow edema as well as edema to the adjacent soft tissues. Bone scanning showed increased uptake of radioisotope in the medial femoral condyle. The patient was diagnosed with bone marrow edema syndrome, and managed medically with analgesics and continued non weight-bearing status. At the 1-month follow-up, his symptoms had improved significantly. The patient progressively increased weight bearing as tolerated over the subsequent weeks. At 12-week follow-up, symptoms had completely resolved. Magnetic resonance imaging showed no signal abnormalities in the affected knee. Transient osteoporosis is an uncommon and typically self-limiting condition that can be challenging to diagnose and treat. The clinician must be aware of this entity, as well as its typical course, to prevent unnecessary testing and invasive intervention.
Keywords: Humans; Knee Joint; Magnetic Resonance Imaging; Male; Middle Aged; Osteoporosis; Tomography, X-Ray Computed; Treatment Outcome